A case study on parents' involvement on children's education - Chela, Chin (University Malaysia Sarawak, (UNIMAS), 2005)
This study is aimed at determining the extent of parents' involvement in children's education, the factors that influence the extent of parents' involvement in children's education and the effects of parents' involvement in children's education. A case study was carried by using the questionnaire which was administered to a group of thirty parents from Than community in Rumah Albert Angang, Sengalang Debak in Betong District. The questionnaires consist of three sections: Section A (Extent of parents' involvement in children's education), Section B (The factors that influence the extent of parents' involvement in children's education, and Section C (The effects of parents' involvement in children's education). The results showed that majority of the parents who involved in this study realized the importance of their involvement in their children's education was vital in improving their children's academic achievement. By getting involved these parents felt that they had performed their part alongside the school and that they were not leaving it to the school alone to educate their children. The results also showed that these parents strongly believed that their involvement in their children's education could bring positive effects toward their children's academic achievement as well as their children's attitude and social behavior, and motivate them in their learning. Based on the findings, suggestions and recommendations for further studies were also discussed.